Sensory Methodologies and Methods: A Scoping Review - Kathleen C. Sitter; Carly-Ann Haney; Ana Herrera; Mica Pabia; Fiona C. Schick; Stacey Squires (Societies, 2025)
This scoping review examines the application of sensory research methodologies and methods in primary research, guided by Arksey and O’Malley’s five-stage framework. The scoping review addresses two primary questions: (1) what is the extent and nature of research activities that use multisensory methodologies and (2) what is the extent and nature of research activities that use multisensory methods? The Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) Checklist was used to guide the reporting and mapping process. A total of 80 sources (45 peer-reviewed articles and 35 dissertations) met the inclusion criteria. Findings reveal ethnographic-based methodologies were the most common sensory approach, whereas combined visual and audio methods were the most commonly used techniques. There is the potential for more innovative and inclusive methodologies and methods to expand the use of taste and smell, which remain underrepresented in the literature. Additionally, greater attention is needed to address power dynamics and reflexivity in sensory research to avoid essentializing or misrepresenting participants’ experiences. Future research could improve methodological clarity and consistency while emphasizing accessibility and community engagement. This scoping review contributes to the field of sensory research by synthesizing current practices and identifying gaps that warrant future exploration, particularly in underrepresented sensory modalities.